Bim contributes to the progression of Huntington's disease-associated phenotypes. (9th December 2019) - Roberts, Sheridan L; Evans, Tracey; Yang, Yi; Fu, Yuhua; Button, Robert W; Sipthorpe, Rebecca J; Cowan, Katrina; Valionyte, Evelina; Anichtchik, Oleg; Li, Huiliang; Lu, Boxun; Luo, Shouqing
Abstract: Huntington's disease (HD) is a neurodegenerative disorder caused by an expanded polyglutamine tract in the huntingtin (HTT) protein. Mutant HTT (mHTT) toxicity is caused by its aggregation/oligomerization. The striatum is the most vulnerable region, although all brain regions undergo neuronal degeneration in the disease. Here we show that the levels of Bim, a BH3-only protein, are significantly increased in HD human post-mortem and HD mouse striata, correlating with neuronal death. Bim reduction ameliorates mHTT neurotoxicity in HD cells. In the HD mouse model, heterozygous Bim knockout significantly mitigates mHTT accumulation and neuronal death, ameliorating disease-associated phenotypes and lifespan. Therefore, Bim could contribute to the progression of HD.